Retinal vessel shift and its association with axial length elongation in a prospective observation in Japanese junior high school students. - Shotaro Asano; Takehiro Yamashita; Ryo Asaoka; Yuri Fujino; Hiroshi Murata; Hiroto Terasaki; Naoya Yoshihara; Naoko Kakiuchi; Taiji Sakamoto (PLoS ONE, 2021)
Purpose To investigate retinal vessel shift (RVS) and its association with axial length (AL) elongation in junior high school students. Methods Total 161 eyes of 161 healthy junior high school students were prospectively studied. Optical AL and anterior chamber depth (ACD) measurements, and fundus photography were performed in the first and third grades. Eyes of subjects in the first and third grade that had perfect matching among all the retinal vessels were allocated to the RVS(-) group, otherwise allocated to the RVS(+) group. In the RVS(+) group, the peripapillary retinal arteries angle (PRAA) was measured for quantitative analysis of RVS; the angle between the major retinal arteries. The variables related to PRAA were identified using model selection with the corrected Akaike information criterion. Results Forty-two eyes (26.1%) were allocated to the RVS(+) group. There were seven patterns in the RVS of those in the RVS(+) group, including clockwise shift in the supra temporal area (5 eyes), infra temporal area (7 eyes), and nasal area (9 eyes); anticlockwise shift in the supra temporal area (7 eyes), infra temporal area (5 eyes), and nasal area (2 eyes); and distal shift in the temporal area (7 eyes). The optimal model for the PRAA narrowing included larger AL and body weight in the first grade, and greater AL elongation. Conclusion Various (seven) RVS patterns were observed in about 25% of the junior high school students within two years. RVS was associated with AL elongation, and useful to reveal the mechanism of myopic retinal stretch.